SYNERGY BETWEEN SCIENCE AND TECHNOLOGY IN ENHANCING THE COMPETENCIES OF ELEMENTARY MADRASAH TEACHER EDUCATION STUDENTS - Muhammad Azhari; Ani Cahyadi; Ainun Mahfuzah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to analyze the synergy between science and technology in enhancing the competencies of Elementary Madrasah Teacher Education students at STAI Al-Falah Banjarbaru. This study employs a qualitative approach with a descriptive design. Data collection techniques included observation, interviews, and documentation of students and faculty members. Data analysis involved the stages of data reduction, data presentation, and drawing conclusions to obtain a systematic overview of the phenomenon under study. The results indicate that the integration of science and technology contributes to enhancing students’ pedagogical, professional, and digital literacy competencies. Students demonstrated improved abilities in designing technology-based learning, integrating scientific concepts into instructional materials, and effectively utilizing digital media. However, several challenges were identified, including limited supporting facilities and varying levels of technological proficiency among students. Thus, the synergy between science and technology plays a crucial role in supporting the enhancement of competencies among students in the Elementary Madrasah Teacher Education program. Therefore, strategic efforts are needed from the institution to strengthen infrastructure support and ensure the continuous development of students’ capacities.